The paradigm model of the knowledge-based society in the Islamic Republic of Iran - Naser Rahmdel; Mehran Keshtkar (مطالعات مدیریت راهبردی, 2021)
Aim and introduction: According to the upstream documents, one of the characteristics of Iranian society in the 20-year perspective is the realization of a knowledge-based society. Identifying the context, causal conditions, interventionist conditions and strategies of knowledge interaction in leading knowledge-based societies can be useful and effective in the realization of the knowledge community. The purpose of this grounded theory based research is identifying and classifying these factors and finding answer the basic question: What are the contexts, causal conditions, interventionist conditions and strategies of knowledge interaction in leading knowledge-based societies? Knowledge is vital to the development of human societies and plays a key role in economic growth, social development, cultural richness and political empowerment. In order to distinguish the knowledge-based society from the "information society", UNESCO has developed the concept of the "knowledge-based society", which contains ideas based on inclusiveness, pluralism, equality, openness and participation. This concept expresses UNESCO's strong belief that “knowledge-based societies should be shaped and guided not only by scientific and technological forces, but also by social choices”. In fact, science and technology create an extraordinary capacity for the exchange of information and knowledge, the emergence of new patterns of communication and the exchange of ideas, as well as the production and design. In fact, each society has its own epistemological capitals. In the Islamic Republic of Iran, the establishment of a knowledge-based society, an educated, capable, entrepreneur, creative, innovative society and the like (Article 4 of the Sixth Five-Year Plan) are among the items mentioned in the upstream documents and specifically the vision document. In addition, the measures announced by the Supreme Leader "Model of Iranian Islamic Development" from the view point of responding to the needs and demands of society and using opportunities to achieve a high level of welfare and prosperity; Realization of knowledge-based society are important. Achieving them requires fundamental attention to mobilizing knowledge resources and capacities to move hopefully and find new, effective, efficient and sustainable solutions to govern society. Methodology: This research has an inductive approach and is qualitative in terms of strategy. It has used grounded theory. Therefore, upstream documents such as Vision 1404, five-year plans, strategic transformation document of science and technology, relevant scientific and research studies and specialized interviews in the period from the second half of 1398 to the end of June 1399 in a semi-structured and snowball method (to Reach the theoretical saturation) was done to identify and explain the effective factors. Researcher collected valid documents for “validity” and selected the research community according to characteristics such as more than 20 years of experience in science and technology policy, activity at high levels (Executives of economic, cultural, political and social centers), higher education and research activities in universities and research centers of the country. In addition, at the end of each coding step, the result provided to five experts to check the scientific accuracy of the research and the degree of compliance of research variables and items with the main purpose of the research. Findings: According to the findings, endogenous knowledge, evolution of production thought, transformation of people from just consuming to producing knowledge, have the most important role in shaping the knowledge-based society, and the main source of these changes are the people. When knowledge leaves the minds of individuals and is in the cycle of distribution and dissemination, it affects all aspects of society. Considering themes such as "common concern and determination"; "fundamental developments based on science and technology" (central class); Creation, distribution and application of knowledge (causal conditions); Social, cultural, economic and information and communication capital (intervening conditions); 20-year vision and the necessity of the evolution of production thought and thinking with a focus on members of society (context); Dynamics, strengthening the relationship between university, industry and government, promoting learning opportunities (strategies) is essential for the realization of a knowledge-based society. Validation of the extracted themes is done by holding a Delphi panel and finally, a paradigm model is presented. Discussion and Conclusion: Fundamental changes have affected the nature of societies. A new order is forming based on knowledge and knowledge based innovation. Because of knowledge, there is irreversible transformation and control for societies. The fact is that despite such an inevitable phenomenon, “a brief acquaintance of the scientific and executive community with the term of knowledge-based society, a clear explanation of the concept, and the recognition of its effective basic elements” have not based on a scientific and logical system. The necessity of this is due: firstly, its origin is non-native literature; and second, it has been examined at organizational or field levels such as knowledge-based economics and the like. The theory of knowledge-based society and one of the most important requirements and foundations for its realization is to change existing mentalities and procedures and believe that knowledge is the greatest asset of any society and, people are the main source of this capital. When knowledge leaves the minds of individuals and is in the cycle of dissemination, it becomes empowering and affects all aspects of society.